Additional Exergames to Regular Tennis Training Improves Cognitive-Motor Functions of Children but May Temporarily Affect Tennis Technique: A Single-Blind Randomized Controlled Trial - Šlosar, Luka; de Bruin, Eling D.; Fontes, Eduardo Bodnariuc; Plevnik, Matej; Pisot, Rado; Simunic, Bostjan; Marusic, Uros (Frontiers in Psychology, 2021)
This study evaluated the effects of an exergame program (TennisVirtua-4, Playstation Kinect) combined with traditional tennis training on autonomic regulation, tennis technique, gross motor skills, clinical reaction time, and cognitive inhibitory control in children. Sixty-three children were randomized into four groups (1st – two exergame and two regular trainings sessions/week, 2nd – one exergame and one regular training sessions/week, 3rd – two regular trainings sessions/week and 4th – one regular training session/week) and compared at baseline, 6-month immediately post intervention and at 1-year follow-up post intervention. At 6-month post intervention the combined exergame and regular training sessions revealed: higher breathing frequency, heart rate (all ps≤0.001) and lower skin conductance levels (p=0.001) during exergaming; additional benefits in the point of contact and kinetic chain elements of the tennis forehand and backhand technique (all ps≤0.001); negative impact on the shot preparation and the follow-through elements (all ps≤0.017); higher ball skills (as part of the gross motor skills) (p<0.001); higher percentages of clinical reaction time improvement (1st -9.7% vs. 3rd group -7.4% and 2nd -6.6% vs 4th group -4.4%, all ps≤0.003) and cognitive inhibitory control improvement in both congruent (1st -20.5% vs. 3rd group -18.4% and 2nd -11.5% vs 4th group -9.6%, all ps≤0.05) and incongruent (1st group -19.1% vs. 3rd group -12.5% and 2nd group -11.4% vs 4th group -6.5%, all ps≤0.001) trials. The 1-year follow-up test showed no differences in the tennis technique, clinical reaction time and cognitive inhibitory control improvement between groups with the same number of trainings per week. The findings support exergaming as an additional training tool, aimed to improve important cognitive-motor tennis skills by adding dynamics to the standardized training process. Caution should be placed to planning this training, e.g. in a mesocycle, since exergaming might decrease the improvement of specific tennis technique parts of the trainees. (ClinicalTrials.gov; ID: NCT03946436).